Pipelines 2011 2011
DOI: 10.1061/41187(420)18
|View full text |Cite
|
Sign up to set email alerts
|

Prestressed Concrete Cylinder Pipe Condition Assessment—What Works, What Doesn't, What's Next

Abstract: This paper presents a summary of the research performed for Water Research Foundation on the evaluation of condition assessment and remaining service life prediction/failure margin analysis technologies in use for prestressed concrete cylinder pipe (PCCP). The project involved a literature review, an industry survey, and a workshop. The literature review integrated the published experiences with all condition assessment and monitoring technologies. The industry survey included design, distribution, and compila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 1 publication
0
26
0
Order By: Relevance
“…Therefore, at this time, it is not possible to account for potential inaccuracies of wire‐break estimates based on electromagnetic inspection in failure‐margin analysis. This point is supported by Zarghamee et al, who have concluded that (1) the actual number of broken wires can differ significantly from the number predicted by nondestructive testing and (2) failure‐margin analyses should be considered preliminary until verification of the predicted number of broken wires is performed on selected pipes through external inspection (Zarghamee et al, 2012; Nardini et al, 2011).…”
Section: Failure Margin Analysismentioning
confidence: 94%
See 2 more Smart Citations
“…Therefore, at this time, it is not possible to account for potential inaccuracies of wire‐break estimates based on electromagnetic inspection in failure‐margin analysis. This point is supported by Zarghamee et al, who have concluded that (1) the actual number of broken wires can differ significantly from the number predicted by nondestructive testing and (2) failure‐margin analyses should be considered preliminary until verification of the predicted number of broken wires is performed on selected pipes through external inspection (Zarghamee et al, 2012; Nardini et al, 2011).…”
Section: Failure Margin Analysismentioning
confidence: 94%
“…Since its introduction, electromagnetic inspection has been used on numerous pipelines nationwide with mixed results (Williams et al, 2012; Bambei et al, 2005; Galleher et al, 2005; Galleher et al, 2000). Application of electromagnetic inspection to pipelines that do not have shorting straps beneath the wire, are composed of lined‐cylinder‐type PCCP, or are under pressurized flow (in‐service) has also been attempted (Williams et al, 2012; Zarghamee et al, 2012; Mergelas et al, 2006). On the basis of data from numerous sources, it is apparent that electromagnetic inspection can identify PCCP with broken wires with variable reliability and accuracy.…”
Section: Condition Assessment Methodologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Identifying individual pipelines or sections of pipelines at highest priority for advanced condition assessment, rehabilitation, and/or monitoring requires ranking sections of the system based on their criticality. Criticality can be determined based on the pipe risk of failure and constraints within the system (Zarghamee et al 2012). This paper focuses on the use of available pipeline data and condition assessment results to calculate the risk of pipe failure and prioritize pipeline repairs.…”
Section: Introductionmentioning
confidence: 99%
“…And two types of PCCP, Embedded Cylinder Pipe and Lined Cylinder Pipe, have been applied since the first application in US in the 1940s [1,2]. Research has been carried out on the operational condition assessment of PCCP with statistical analysis [1,[3][4][5], experiments [6,7], and numerical modeling [8,9]. These studies have shown that PCCP have low levels of damage and low distress rate as compared to conventional concrete pipes.…”
Section: Introductionmentioning
confidence: 99%